Pendidikan Islam Dalam Pendidikan Moral Dan Etika Anak Usia Dini Di Raudhatul Athfal Al-Kifayah Pekanbaru - Haryuni Hariati (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
The moral and behavioral decline among adolescents in the modern era has reached an alarming level, as evidenced by the increasing prevalence of violent acts such as homicide, assault, rape, bullying, and theft. In this context, Islamic education serves a pivotal role in strengthening moral education and shaping virtuous character. This study aims to explore the conceptual implementation of Islamic education in enhancing the moral development of students. Employing a descriptive analytical approach, the research investigates how Islamic values can be systematically integrated into educational frameworks to foster ethical awareness and personal integrity. Islamic education is regarded as a foundational pillar in cultivating both individual character and national identity, as it instills, nurtures, and operationalizes ethical principles not only for personal refinement but also for fostering a morally responsible and civically engaged society